microRNA miR-142-3p Inhibits Breast Cancer Cell Invasiveness by Synchronous Targeting of WASL, Integrin Alpha V, and Additional Cytoskeletal Elements. - Alexander Schwickert; Esther Weghake; Kathrin Brüggemann; Annika Engbers; Benjamin F Brinkmann; Björn Kemper; Jochen Seggewiß; Christian Stock; Klaus Ebnet; Ludwig Kiesel; Christoph Riethmüller; Martin Götte (PLoS ONE)
MicroRNAs (miRNAs, micro ribonucleic acids) are pivotal post-transcriptional regulators of gene expression. These endogenous small non-coding RNAs play significant roles in tumorigenesis and tumor progression. miR-142-3p expression is dysregulated in several breast cancer subtypes. We aimed at investigating the role of miR-142-3p in breast cancer cell invasiveness. Supported by transcriptomic Affymetrix array analysis and confirmatory investigations at the mRNA and protein level, we demonstrate that overexpression of miR-142-3p in MDA-MB-231, MDA-MB-468 and MCF-7 breast cancer cells leads to downregulation of WASL (Wiskott-Aldrich syndrome-like, protein: N-WASP), Integrin-αV, RAC1, and CFL2, molecules implicated in cytoskeletal regulation and cell motility. ROCK2, IL6ST, KLF4, PGRMC2 and ADCY9 were identified as additional targets in a subset of cell lines. Decreased Matrigel invasiveness was associated with the miR-142-3p-induced expression changes. Confocal immunofluorescence microscopy, nanoscale atomic force microscopy and digital holographic microscopy revealed a change in cell morphology as well as a reduced cell volume and size. A more cortical actin distribution and a loss of membrane protrusions were observed in cells overexpressing miR-142-3p. Luciferase activation assays confirmed direct miR-142-3p-dependent regulation of the 3'-untranslated region of ITGAV and WASL. siRNA-mediated depletion of ITGAV and WASL resulted in a significant reduction of cellular invasiveness, highlighting the contribution of these factors to the miRNA-dependent invasion phenotype. While knockdown of WASL significantly reduced the number of membrane protrusions compared to controls, knockdown of ITGAV resulted in a decreased cell volume, indicating differential contributions of these factors to the miR-142-3p-induced phenotype. Our data identify WASL, ITGAV and several additional cytoskeleton-associated molecules as novel invasion-promoting targets of miR-142-3p in breast cancer.